Tracing the narrativity of National Geographic feature articles in the light of evolving media landscapes. (December 2017) - Pflaeging, Jana
Abstract: This article seeks to trace the narrativization of the genre feature article as published in the National Geographic magazine over the past 100 years. I base my argumentation on the observation that image-caption-clusters have gained remarkable prominence in perception as they today often cover the entire layout space of a double-page, when they often appeared together with running text on a 1915 spread. Given that narrativization has always been a core popularization strategy of the magazine's journalistic practices, and is thus likely to be expected by its audience, the question arises whether perceptually prominent image-caption-clusters have increased in their degree of narrativity . In order to explore this question, I establish an interdisciplinary framework for a media linguistic analysis of literary journalism inspired by theorization in linguistics, literary studies, narratology and its cognitive branches. I proceed by exploring a corpus of altogether 15 National Geographic print feature articles (and their 304 image-caption-clusters) published in 1915, 1965, and 2015. I conclude this paper with a discussion of my findings. In particular, I draw on the framework of audience design and outline five main aspects magazine editors are at least likely to consider when making assumptions about their audience's genre expectations.